Physical Education Learning Management in Fostering Students' Kinesthetic Intelligence - Achmad Pahrul Rodji; Novi Rukhviyanti; Sepryhatin Dioputra (International Journal of Social Service and Research, 2022)
Kinesthetic-based physical education learning has an excellent opportunity to develop multiple intelligences in students at school. Physical education carried out in schools can help students improve motor skills, health, fitness, character formation, personality, and discipline, and instill the values ??of honesty, cooperation, and responsibility. Currently, the reality of teachers in the field does not understand the role of physical education in the educational process, and most teachers argue that sport is only for maintaining health and has not yet reached the role of physical education in supporting the development of children's intelligence. This study aimed to see how far the implementation of physical education in improving kinesthetic intelligence in Madrasah Ibtidayyah (MI) Al-Firdaus and MI Yanuri is through a management approach. In particular, this study describes the principles of management theory, including: (1) planning, (2) organizing, (3) implementing, and (4) evaluating physical education and its relationship with kinesthetic intelligence using management theory from GR Terry and Howard Gardner's theory of kinesthetic intelligence. This study uses a descriptive method with a qualitative approach and data collection by conducting observations, interviews, and documentation studies. The study results indicate that the management of physical education in fostering kinesthetic intelligence in the two Madrasah Ibtidaiyah has been carried out by adjusting the existing theoretical principles and concepts. However, its implementation still has obstacles, especially in the facilities and infrastructure supporting physical education learning.